Various medicinal plants traded in the village market of Karangwangi Village, Southern Cianjur, West Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Iskandar BS, Iskandar J, Partasasmita R, Irawan B. 2020. Various medicinal plants traded in the village market of Karangwangi Village, Southern Cianjur, West Java, Indonesia. Biodiversitas 21: 4440-4456. In the past traditional village, the market was predominantly found in many villages of West Java. The village markets were usually held once a week. The traders of the village market mainly were from both local villagers or people coming from the nearby towns. Nowadays, the village markets of West Java have dramatically decreased because of the existence of permanent shops (toko) and minimarkets in the rural areas that operate daily. However, in some villages, such as Karangwangi Village, Cidaun Sub-district, Southern Cianjur, West Java, village markets still exist. In the Karangwangi Village market, various plants are commonly traded, such as staple foods, vegetables, fruits, spices, and traditional medicines. The purpose of this study was to discuss the various traditional medicinal plants traded in the village market, some diseases treated by the various herbal plants, various plant parts used for traditional medicines, and original medicinal plants in the village markets of Karangwangi Village. The research method used was qualitative, with data collection carried out by observation, by recording various traditional medicinal plants traded in the village market, and by interviewing informants regarding the use of each medicinal plant species for the treatment of diseases and the origin of plant traded in village markets. The results of the study showed that 35 species representing 23 families of the medicinal plant were documented to be traded in the traditional village markets of Karangwangi Village. These plants are predominantly used to treat 20 kinds of diseases and other disturbance conditions, namely anemia, cough, fever, diabetes, wound, gastritis, malaria, bruised, supplement, toothache, kidney disease, mouth sores, stomachache, high blood pressure, postpartum healing, low back pain, urinary disease, rich breastfeeding produce, dermatitis, and gastroenteritis. Plant parts used for medicinal ingredients in the form of leaf, fruit, bulb, rhizome, root, seed, and shoot. Some medicinal plants have been known to have dual function, such as medicine and vegetables (13 species (36.36%)), medicines and herbs (12 species (34.28 %)), medicines and spices (10 species (28.57 %)), medicines and fruits (8 species (22.85 %)), medicines and staple food (3 species (8.57 %)), medicines, vegetables and spices (1 species (2.85 %)), and medicine and to betel ingredient (1 species (3.03%)). Most of the origin of medicinal plants traded in the village market is from the village with 23 species (65.71%), from cities with 9 species (25.71%), and from both villages and cities with 3 species (8.57 %). On this basis, it can be concluded that the traditional village market has played an important role not only for social-economic interests but also for biodiversity conservation, including biological ingredients for traditional medicines of the rural communities.
Keywords: Diseases, medicinal plants, village market, West Java